Application of desirability function based response surface methodology (DRSM) for investigating the plasma arc cutting process of sailhard steel. (6th August 2018) - Naik, Deepak Kumar; Maity, Kalipada
Abstract : Purpose: Plasma arc cutting (PAC) is extensively applicable for cutting the materials in faster speed with better accuracy in different manufacturing industries. The cutting of sailhard steel plate plays a great challenge in plasma arc cutting process. Design/methodology/approach: In this investigation, a special abrasion-resistant steel known as sailhard of 20 mm thickness plate has been cut by PAC machine. Cutting current, stand-off distance, cutting speed and gas pressure were selected as cutting parameters. The corresponding responses focused for this study are material removal rate, kerf and chamfer. L30 orthogonal array based on a central composite design (CCD) of response surface methodology (RSM) was used to design the run of the experiment. For predicting and modeling of optimal cutting conditions, a hybrid approach of desirability function-based response surface methodology (DRSM) was acquainted. Findings: The result of this study determines that desirability index (DI) was affected significantly with the machining parameter as well as their interaction. A confirmation test was carried out to analyze the degree of effectiveness of DRSM technique. Originality/value: In PAC, the selection of process parameters and effect of that parameter on the output responses is of greater value because of the selection of best cutting condition.